POLA BELAJAR PESERTA DIDIK DALAM PROGRAM BELAJAR DARI RUMAH - Ufairoh, Nahda Yumna; Purnamasari, Iin; Sulianto, Joko (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2022)
The purpose of this reseach was to analyze the implementation of the BDR program, student learning patterns at SD Negeri Mojoagung 01, Pati, Central Java. This type of research is qualitative which is presented in the form of a description. The research data was obtained from the results of filling out questionnaires and interviews involving parents, teachers, and students of SD Negeri Mojoagung 01. The results of the analysis of questionnaires and interviews showed that the BDR program at SD Negeri Mojoagung 01 was carried out in a blended manner. The learning patterns of students at SD Negeri Mojoagung 01 are cognitive and aesthetic learning activities; visual, auditory, kinesthetic learning styles; forms of self-study, group, tutorial; playing games, listening to music, watching TV, playing with younger siblings to relieve boredom of studying; comfortable learning places are study tables, rooms, family rooms, dining tables; quiet learning atmosphere, accompanied by music, any atmosphere.